Difficulties of scientific research in the financial and administrative fieldaccording to the quality standardsfrom the point of view of the teachers (Journal of Accounting and Financial Studies ( JAFS ), 2018)
The research aims to identify the most important difficulties facing the scientific research in the technical university in the financial, organizational and administrative according to the quality standards according to the paragraphs studied in the questionnaire questionnaire prepared for this purpose, including the research community on the Central Technical University, which includes several technical colleges and technical institutes were selected A sample of the researchers in the Institute of Technical Management where the number of training was 78 teachers took a random sample of researchers amounted to 40% of the questionnaire, and after the collection and classification of data were used statistical means, including the mean arithmetic and relative weight, The most important difficulties facing teachers in the financial field, the weakness of the budget allocated for scientific research and the difficulty of obtaining financial and accounting information in the field of institutions and companies concerned with the search and blocking of financial and accounting information under the pretext of confidentiality and security data and information. The material expenses of teaching participation in scientific conferences outside the country and the large number of tasks and the size of the teaching burden in addition to the preference for additional teaching work to carry out scientific research and the research has been Of the recommendations and proposals that serve the research.